Disentangling the Effects of an Adult Model's Eye Gaze and Head Orientation on Young Infants' Processing of a Previously Attended Object. (7th September 2013) - Hoehl, Stefanie; Wahl, Sebastian; Pauen, Sabina
<x xml:space="preserve">Abstract</x> In order to disentangle the effects of an adult model's eye gaze and head orientation on infants' processing of objects attended to by the adult, we presented 4‐month‐olds with faces that either (1) shifted eye gaze toward or away from an object while the head stayed stationary or (2) that turned their head while maintaining gaze directed straight ahead. Infants' responses to the previously attended and unattended objects were measured using eye‐tracking and event‐related potentials. In both conditions, infants responded to objects that were not cued by the adult's head or eye gaze shift with more visual attention and an increased negative central (Nc) component relative to cued objects. This suggests that cued objects had been encoded more effectively, whereas uncued objects required further processing. We conclude that eye gaze and head orientation act independently as cues to direct infants' attention and object processing. Both head orientation and eye gaze, when presented in motion, even override the effects of incongruent stationary information from the other kind of cue.